The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1186/s12879-016-2110-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of bla OXA-23 -producing carbapenem-resistant Acinetobacter baumannii in a single institution over a 65-month period in north China

Abstract: BackgroundCarbapenem-resistant Acinetobacter baumannii poses a significant threat to hospitalized patients, as few therapeutic options remain. Thus, we investigated the molecular epidemiology and mechanism of resistance of carbapenem-resistant A.baumannii isolates in Beijing, China.MethodsCarbapenem-resistant A.baumannii isolates (n = 101) obtained between June 2009 and November 2014 were used. Multilocus sequence typing (MLST) and PCR assays for class C and D β-lactamase were performed on all isolates. S1 nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 50 publications
3
24
1
Order By: Relevance
“…The major sequence types (ST) in this study were ST191 and ST195, which were previously reported as the major STs carrying carbapenem-resistance gene bla OXA-23 in the carbapenem-resistance A. baumannii in China. 22 Consistently, all ST191 and ST195 isolates in our study carrying a single copy of bla OXA-23 were shown to be resistant to carbapenem antibiotics. Interestingly, the survival rate of two ST191 isolates (402 and N10) was similar to AB5057, a model highly virulent A. baumannii strain, 23 but the survival rate of six ST195 isolates (401, 405-408, N29) was significantly higher than AB5075 (p < 0.05).…”
Section: Discussionsupporting
confidence: 78%
“…The major sequence types (ST) in this study were ST191 and ST195, which were previously reported as the major STs carrying carbapenem-resistance gene bla OXA-23 in the carbapenem-resistance A. baumannii in China. 22 Consistently, all ST191 and ST195 isolates in our study carrying a single copy of bla OXA-23 were shown to be resistant to carbapenem antibiotics. Interestingly, the survival rate of two ST191 isolates (402 and N10) was similar to AB5057, a model highly virulent A. baumannii strain, 23 but the survival rate of six ST195 isolates (401, 405-408, N29) was significantly higher than AB5075 (p < 0.05).…”
Section: Discussionsupporting
confidence: 78%
“…Population structure of the isolates was quite variable with five different STs reported. ST 195 was previously reported in China and associated with OXA-23 β-lactamase in contrast with our study in which this ST was found in OXA-40 positive isolates [46][47] . In both studies ST195 isolates belonged to IC II.…”
Section: Genotypingcontrasting
confidence: 56%
“…While carbapenems have the most extended spectrum of antibacterial activity of all the beta‐lactams, the carbapenem resistance rate in A. baumannii has reached more than 50% worldwide in the past decade as reported in previous studies (Chagas et al ; Wang et al ; Ning et al ; Pfeifer et al ; Rieber et al ). Overall, CRAB isolates are resistant to multiple drugs which forcefully contribute to further outbreaks due to the limited treatment alternatives (Migliavacca et al ; Ning et al ; Rieber et al ). Meanwhile, 100% of our CRAB isolates were MDR and 50% were XDR, which makes the treatment of these isolates difficult; therefore, prescribing carbapenem in combination with other antibiotics, especially aminoglycosides, cephalosporins, colistin, and TG, is recommended for the effective treatment of resistant isolates (Farsiani et al ).…”
Section: Discussionmentioning
confidence: 70%
“…Of these, OXA‐51 is intrinsic and the acquisition of other CHDL genes occurs through plasmids, integrons, or transposons. In addition to β‐lactamases, increased activity of multidrug efflux pumps, decreased permeability of cell membranes, or modified penicillin‐binding proteins can give rise to the emergence of CRAB strains (Franolić‐Kukina et al ; Amiri et al ; Ning et al ). Meanwhile, insertion sequences (ISs) are mobile genetic elements that can serve as a strong promoter for resistance genes.…”
Section: Introductionmentioning
confidence: 99%